Now you see me, now you don't [videorecording (DVD)] - Tyler, Brian (Composer) (Lionsgate, 2026)
"The Four Horsemen have returned--to unite with a new generation of illusionists for their most global, high-stakes adventure yet. Their mission: Expose the corruption of Veronika Vanderberg, a powerful diamond heiress with ties to arms dealers, traffickers, and warlords. Aided by legendary magician Thaddeus, the two teams must overcome their differences to try and defeat their cunning and dangerous adversary."--